Beyond human : vital materialisms in the Andean avant-gardes - Daly, Tara (Bucknell studies in Latin American literature and theory., 2019)
"By presenting fresh readings of canonical authors like César Vallejo, José María Arguedas, and Magda Portal and through analysis of newer artist-activists like Julieta Paredes, Mujeres Creando Comunidad, and Alejandra Dorado, Daly argues that avant-gardes complicate questions of agency and contribute to theoretical discussions on vital materialisms"--